Question about Bagatrix Algebra Solved! 2005 (105101) for PC

# 3x = 4y = -12 - Bagatrix Algebra Solved! 2005 (105101) for PC

Posted by on

• Level 3:

An expert who has achieved level 3 by getting 1000 points

All-Star:

An expert that got 10 achievements.

MVP:

An expert that got 5 achievements.

Guru:

An expert who has written 7 tips or uploaded 3 video tips

• Master

X = -4, y = -3

Posted on Nov 11, 2010

Hi,
A 6ya expert can help you resolve that issue over the phone in a minute or two.
Best thing about this new service is that you are never placed on hold and get to talk to real repairmen in the US.
The service is completely free and covers almost anything you can think of (from cars to computers, handyman, and even drones).
Good luck!

Posted on Jan 02, 2017

×

my-video-file.mp4

×

## Related Questions:

### (3x-4y)*(3x-4y)

9x^2 - 24xy + 16y^2

If this is homework, be sure to show your work.

Oct 21, 2016 | Computers & Internet

### Find the equations of circles passing through (1,-1),touching the lines 4x+3y+5=0 and 3x-4y-10=0

First, I graphed the lines and the point using Desmos.com.

I noticed that the two lines are perpendicular to each other and the point (1,-1) appears to be on the right side of the circle, on a line parallel to 3x -4y-10=0. The equation of this line is y= 3/4x - 1.75. The y-intercept is -1.75. Now we have two points on the opposite sides of the circle, (1, -1) and (0,-1.75). The midpoint formula will give you the centre of the circle and the distance formula will provide the radius.

Let me know if you have any questions.

Good luck.

Paul
Desmos Beautiful Free Math

Jun 09, 2014 | Office Equipment & Supplies

### 3x + 4y =6

That's the equation of a line. Do you have a question about it?

Nov 23, 2013 | Computers & Internet

### Definition of special product in algebra types and example of special product in algebra

Product means the result you get after multiplying.
In Algebra xy means x multiplied by y
Likewise when you see (a+b)(a-b) it means (a+b) multiplied by (a-b), which we will be using a lot here!
Special Binomial Products So when you multiply binomials you get ... Binomial Products
And we are going to look at three special cases of multiplying binomials ... so they are Special Binomial Products.
1. Multiplying a Binomial by Itself What happens when you square a binomial (in other words, multiply it by itself) .. ?

(a+b)2 = (a+b)(a+b) = ... ?

The result:

(a+b)2 = a2 + 2ab + b2
You can easily see why it works, in this diagram:

2. Subtract Times Subtract And what happens if you square a binomial with a minus inside?

(a-b)2 = (a-b)(a-b) = ... ?

The result:

(a-b)2 = a2 - 2ab + b2
3. Add Times Subtract And then there is one more special case... what if you multiply (a+b) by (a-b) ?

(a+b)(a-b) = ... ?

The result:

(a+b)(a-b) = a2 - b2
That was interesting! It ended up very simple.
And it is called the "difference of two squares" (the two squares are a2 and b2).
a2 - b2 is equal to (a+b)(a-b) Note: it does not matter if (a-b) comes first:

(a-b)(a+b) = a2 - b2
The Three Cases Here are the three results we just got:
(a+b)2 = a2 + 2ab + b2 } (the "perfect square trinomials") (a-b)2 = a2 - 2ab + b2 (a+b)(a-b) = a2 - b2 (the "difference of squares") Remember those patterns, they will save you time and help you solve many algebra puzzles.
Using Them So far we have just used "a" and "b", but they could be anything.
Example: (y+1)2
We can use the (a+b)2 case where "a" is y, and "b" is 1:

(y+1)2 = (y)2 + 2(y)(1) + (1)2 = y2 + 2y + 1

Example: (3x-4)2
We can use the (a-b)2 case where "a" is 3x, and "b" is 4:

(3x-4)2 = (3x)2 - 2(3x)(4) + (4)2 = 9x2 - 24x + 16

Example: (4y+2)(4y-2)
We know that the result will be the difference of two squares, because:

(a+b)(a-b) = a2 - b2
so:

(4y+2)(4y-2) = (4y)2 - (2)2 = 16y2 - 4
Sometimes you can recognize the pattern of the answer:
Example: can you work out which binomials to multiply to get 4x2 - 9
Hmmm... is that the difference of two squares?
Yes! 4x2 is (2x)2, and 9 is (3)2, so we have:

4x2 - 9 = (2x)2 - (3)2
And that can be produced by the difference of squares formula:

(a+b)(a-b) = a2 - b2
Like this ("a" is 2x, and "b" is 3):

(2x+3)(2x-3) = (2x)2 - (3)2 = 4x2 - 9
So the answer is that you can multiply (2x+3) and (2x-3) to get 4x2 - 9

Jul 26, 2011 | Computers & Internet

### 2x^5+4x^4-3x^2+7,7x^4-3x^3+x^2-9

5x -2(x-2) = 6 -2(-3x-3)
5x -2x +4 = 6 +6x +6 (use the distributive property)
3x + 4 = 6x + 12 (collect terms)
4 = 3x + 12 (subtract 3x from both sides to get all x on one side)
-8 = 3x (subtract 12 from both sides to get only x on one side)
-8/3 = x (divide both sides by 3 to get x by itself)

Check
5(-8/3) -2((-8/3)-2) = 6 - 2(-3(-8/3)-3)
-40/3 -2(-8/3-6/3) = 6 - 2(8-3)
-40/3 -2(-14/3) = 6 -2(5)
-40/3 + 28/3 = 6 - 10
-12/3 = -4 (yes)

Dec 19, 2010 | Answer Racing Ion Motorcycle Jersey 2010

### How do I solve x and y in the following equations? 5x+3y=6 2x-4y=5 Thank you

You can solve it with following method.

5x+3y=6 2x-4y=5
So 5x=6-3y so 2[(6-3y)/5]-4y=5
So x=(6-3y)/5 so 12-6y-20y=25
so -26y=25-12
so -26y=13
so y= -(1/2)
2x-4y=5
so 2x=5+4y
so 2x=5+4(-1/2)
so 2x=(10-4)/2
so 2x=6/4
so x =3/2

The value of x=3/2 and value of y= -1/2

Let me know if you need further assistance.
Thanks for using FixYa.

Mar 03, 2010 | Office Equipment & Supplies

#### Related Topics:

27 people viewed this question

Level 2 Expert

Level 3 Expert